CONCEPT OF IMPLEMENTING CBE (COMMUNITY BASED EDUCATION) IN INDONESIA - Lasadara, Lasadara; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:Community-based education begins with a critical educational perspective that wants to challenge the government's hegemony in the field of education through the democratization of education. This study aims to examine the concept of community-based education that is applied in Indonesia. This study is library research with analysis through a survey of relevant literature data, both in the form of reference books, previous research results, articles, notes, and journals. The results of the study indicate that community-based education in Indonesia has been implemented through various programs developed in the education process in the form of formal and non-formal education rights according to religious characteristics and social and cultural environments. However, there are several obstacles to its implementation in Indonesia, including 1) the relatively high level of community dependence on the government, 2) the weak economy of the community, and 3) school-based education still being dominant. Some supporting factors include: 1) many community-based institutions have succeeded in implementing this model independently, 2) the culture of the Indonesian people who are predominantly Muslim, and 3) the spirit of cooperation.Keywords: